1993
DOI: 10.1002/cc.36819938204
|View full text |Cite
|
Sign up to set email alerts
|

Academic advising, retention, and transfer

Abstract: As the only structured service on campus that guarantees students some kind of interaction with a concerned representative of the institution, academic advising is critical for student retention and successful transfer.Students come to two-year colleges with a variety of goals-to take a few classes for personal enrichment or specific job training, to earn a one-year certificate, to earn a two-year degree in preparation for employment, or for continued education in a four-year college or university. Those of us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The finding is complemented by a study conducted by King (1993) that revealed that academic advising at the community college positively impacted the social adjustment of transfer students in STEM.…”
Section: Downloaded By [Seton Hall University] At 15:41 04 April 2015mentioning
confidence: 72%
“…The finding is complemented by a study conducted by King (1993) that revealed that academic advising at the community college positively impacted the social adjustment of transfer students in STEM.…”
Section: Downloaded By [Seton Hall University] At 15:41 04 April 2015mentioning
confidence: 72%
“…Some of these obstacles have the potential to impact persistence decisions from the outset. Despite Barnett's (2011) observation that we need a greater focus on community college classroom practices related to persistence, it remains true that, at least for the first weeks, an entering community college student's experience is characterized as much by the classroom experience as it is by early procedures and processes such as registration, placement, orientation, financial aid, and particularly academic advising (King, 1993). Even seemingly less critical intake procedures have been connected to student persistence within the community college literature such as registration timing (Hale & Bray, 2011;Smith, Street, & Olivarez, 2002) and course adding and dropping behaviors (Hagedorn, Maxwell, Cypers, Moon, & Lester, 2007).…”
mentioning
confidence: 99%
“…Among early intake activities, the role of academic advising in particular has been connected to student persistence (King, 1993;Young, Backer, & Rogers, 1989), even as relatively few studies have presented empirical evidence supporting these claims (Bailey & Alfonso, 2005). What evidence we do have is in fact sparse and largely based on student perceptions of the quality of advising (Elliott & Healy, 2001;Metzner, 1989;Metzner & Bean, 1987) and frequency of advising sessions (Shields, 1994;Swecker, Fifolt, & Searby, 2013) rather than the nature and scope of issues addressed and tasks completed during advising sessions.…”
mentioning
confidence: 99%
“…As such, academic advising has a direct impact on transfer student transition in a variety of ways. The support of faculty advisors and advising departments also plays a key role in helping students become integrated within the academic and social systems on campus (King, 1993).…”
Section: The Support Of Facultymentioning
confidence: 99%
“…Faculty and academic advising can be seen as the hub of the student services wheel, providing the linkages with other support services, such as career development, counseling centers, offices of financial aid, and tutoring services (King, 1993). In these ways, the faculty member of the Transfer Seminar would be positioned and prepared to assist transfer students in a variety of ways.…”
Section: Recommendations For Practicementioning
confidence: 99%